PERBEDAAN PENERAPAN MODEL PEMBELAJARAN KOOPERATIF ANTARA TIPE THINK PAIR SHARE (TPS) DAN TIPE TWO STAY TWO STRAY (TSTS) BERDASARKAN GAYA KOGNITIF SISWA - Hanifah Eka Wati (PENDAS MAHAKAM: Jurnal Pendidikan dan Pembelajaran Sekolah Dasar, 2016)
The diversity of the student's way of thinking is a uniqueness that is owned by each student. Therefore, as part of efforts to improve students' mathematics learning outcomes is with the selection of appropriate learning models in the learning of mathematics by observing the different cognitive styles of students. This study aims to determine differences in learning outcomes of students who are taught by learning model type koopeeratif think pair share and cooperative learning model two stay two stray based cognitive styles of students of class VII SMP Negeri 5 Samarinda. The research type of research used in this study is quasi-experimental. The population of this research is student class VII 5 Samarinda 2012-2013 school year. Experimental unit of the population selected by cluster random sampling, but previously made the initial observation to determine the cognitive styles of students from 12 classes. Samples were selected grade class VIIE VIIa and then at random to determine the learning model of each class. The learning model in question is the type of learning model koopeeratif think pair share and cooperative learning model two stay two stray. While cognitive style in question is a cognitive style field independent (FI) and cognitive style field dependent (FD). Treatment in this experiment for the class 2 VIIa class taught by cooperative learning model Think Pair Share and VIIE class taught by cooperative learning model two stay two stray. Instruments used in this research is to test cognitive style GEFT and math achievement test. The data obtained were analyzed using descriptive statistics and inferential statistical analysis using comparative analysis and linear regression analysis ganda.Hasil this study indicate that the mathematics learning outcomes in cognitive, affective and psychomotor class VII SMP Negeri 5 Samarinda influenced by cooperative learning model and cognitive styles of students.